수소 스파크점화 엔진의 저부하 운전에서 열효율 및 질소산화물 배출 개선을 위한 배기가스재순환과 과잉공기 전략 비교 - 박현욱; Hyunwook Park; 이준순; Junsun Lee; 오승묵; Seungmook Oh; 이용규; Yonggyu Lee; 김창업; Changup Kim (한국분무공학회지, 2024)
This study compared exhaust gas recirculation (EGR) and excess air strategies for improving thermal efficiency and emissions of hydrogen combustion engines at low-load operation. The experimental investigation was conducted in a single-cylinder, heavy-duty engine under throttling and wide-open throttle (WOT) conditions. Although both EGR and excess air strategies reduced peak heat release rates and increased combustion durations, the net indicated thermal efficiencies were improved by reducing the pumping losses. Under the constraint of similar nitrogen oxides emissions, the EGR strategy had higher net indicated thermal efficiencies compared to the excess air strategy in throttling operation. However, the difference between their thermal efficiencies was reduced under WOT condition. The trend of reducing nitrogen oxides emissions according to the two strategies was similar.